Public Insurance and Wealth Inequality - A Euro Area Analysis - Lien Pham-Dao (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Since the release of the first wave of the Household Finance and Consumption Survey, the causes of the large euro area differences in private net wealth inequality have been at the forefront of the political debate. This paper assesses the quantitative importance of cross-country differences in labor market risks and social security institutions for euro area differences in private net wealth inequality. I document the empirical puzzle that euro area countries with the largest reduction in the income Gini coefficient through public transfers and with most generous welfare states, robustly show a higher inequality in private net wealth. Going back to the argument by Hubbard et al. (1995) that public insurance crowds out private savings especially of the poor, I construct a life cycle model with heterogeneous households and incomplete markets that features exogenous labor market risks, social transfers and public and occupational pensions. Calibrating the model to the actual euro area differences in the gross earnings process, unemployment dynamics and social security systems, it can account for 61.2% of the cross-country differences in the net wealth Gini coefficients for the bottom 95% of the wealth distribution. The model results suggest that welfare policies contribute with 47.3% to the wealth inequality differences across the euro area, while gross earnings inequality and unemployment can rationalize 13.9%.
Keywords: D31; D91; E21; 330